LARGE-SCALE COLONISATION OF THE SPAT OF MUSSEL, MYTILUS VIRIDIS, IN COCHIN REGION - Nair, R V; Nayar, K Nagappan; Mahadevan, S (Indian Journal of Fisheries, 2011)
Large-scale colonisation of the spat of the green mussel, Mytilus viridis, aspecies heretofore considered as not existing in sizable quantities in the Cochinregion, was noticed on the anti-erosicm granitestone embankments of AndakaranAzhi beach between Shertalai and Cochin. The spat, which appear to settle duringthe postfflonsoon period, grow in profusion in the midlittoral and infralittoralregions. The density of the population varies from surface to surface even on asingle boulder. A marked concentration is noticed in the sheltered, dark nichesbeneath the stores, while the flat upper surfaces that are constantly exposed tosevere wave actions appear to be least suitable for mussel growth. It was estimatedthat on an average, 220-248 spat|100 Cm' were in areas submerged most of thetime, while 112-170, in less favourable surroundings. The population which isdensest at Andakaran Azhi diminishes gradually northwards. But on the whole,the potentiality of this resource is large enough to provide ample seed for extensiveculture operations along this region